VIRTUAL LABORATORY FOR COMPUTER-AIDED DESIGN OF BIOSENSORS - Palagin, O.; Romanov, V.; Galelyuka, I.; Kachanovska, M. (International Journal of Computing, 2014)
Fast development of information technologies puts strict requirements to terms and costs of designing of computer devices and systems. These requirements may be fulfilled with help of virtual methods of designing, which are realized by means of virtual laboratories of computer-aided design.